A cellular protein specifically binds to the 3＇ -terminal sequences of hepatitis C virus intermediate negative-strand RNA - 王巍 邓庆丽 黄开红 段朝晖 邵静 黄志清 黄志明 (Chinese medical journal, 2003)
Objective To study the mechanism of the cellular proteins involved in the process of replication of hepatitis C virus (HCV) negative-strand RNA.Methods Ultraviolet (UV) cross-linking was used to identify the cellular proteins that would bind to the 3'-end of HCV negative-strand RNA. Competition experiment was used to confirm the specificity of this binding, in which excess nonhomologous protein and RNA transcripts were used as competitors. The required binding sequence was determined by mapping, then the binding site was predicted through secondary structure analysis.Results A cellular protein of 45 kD (p45) was found to bind specifically to the 3'-end of HCV negative-strand RNA by UV cross-linking, nhomologous proteins and RNA transcripts could not compote out this binding, whereas the unlabeled 3' -end of HCV negative-strand RNA could. Mapping of the protein-binding site suggested that the 3'-end 131-278nt of HCV negative-strand RNA was the possible protein-binding region. Analysis of RNA secondary structure presumed that the potential binding site was located at 194-GAAAGAAC-201.Conclusion The cellular protein p45 could specifically bind to the secondary structure of the 3'-end of HCV intermediate neaative-strand RNA， and mav [~lav an important rnle in HC.V RNA renlic.Atinn